FROM STORIES TO SALES: HOW STORYTELLING MARKETING AFFECTS PURCHASE DECISIONS THROUGH THE MEDIATING ROLE OF BRAND IMAGE - Mandala, Mukti Arya; Aliyah, Kisti Nur (Master of Management Diponegoro University, 2025)
This study aims to analyze the effect of storytelling marketing on social media on the purchase decisions of Ventela shoes, with brand image as a mediating variable among Generation Z in Solo Raya. A quantitative method was employed, involving 100 respondents selected through purposive sampling. Data were collected via an online questionnaire distributed through Google Forms and analyzed using Structural Equation Modeling (SEM) with SmartPLS 3 software. The results revealed that storytelling marketing has a positive and significant effect on brand image (t-statistic = 25.371; p-value = 0.000) and purchase decisions (t-statistic = 5.603; p-value = 0.000). Furthermore, brand image was found to have a positive and significant effect on purchase decisions (t-statistic = 2.094; p-value = 0.037). In addition, brand image significantly mediates the relationship between storytelling marketing and purchase decisions (t-statistic = 2.038; p-value = 0.042). These findings indicate that Ventela’s storytelling marketing strategy on social media effectively enhances brand image and encourages Generation Z to purchase Ventela products.